2007
DOI: 10.1210/en.2006-1233
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Melanocortin Signaling in Refeeding-Induced Neuronal Activation and Satiety

Abstract: To identify regions in the hypothalamus involved in refeeding and their regulation by alpha-MSH, adult rats were subjected to a 3-d fast, and 2 h after refeeding, the distribution of c-Fos-immunoreactive neurons was elucidated. Compared with fed and fasted animals, a significant increase (P < 0.001) in the number of c-Fos-immunoreactive cells was identified in refed animals in the supraoptic nucleus, magnocellular and ventral parvocellular subdivisions of the hypothalamic paraventricular nucleus (PVNv), and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 55 publications
9
50
0
Order By: Relevance
“…These results are in agreement with data previously described, which show that refeeding activates ARC and PVN neurons, indicating that these nuclei also are implicated in the responses associated with satiety (39). Activation of parvocellular PVN in response to food intake is likely to involve vagal innervation, since vagotomy abolishes the activation of this region induced by feeding (47).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in agreement with data previously described, which show that refeeding activates ARC and PVN neurons, indicating that these nuclei also are implicated in the responses associated with satiety (39). Activation of parvocellular PVN in response to food intake is likely to involve vagal innervation, since vagotomy abolishes the activation of this region induced by feeding (47).…”
Section: Discussionsupporting
confidence: 93%
“…It was previously shown that ARC neurons participate in the regulation of food intake during the early phase of refeeding (39). NPY in the ARC is known to increase food intake; thus we can predict that NPY neurons would not be activated in the ADX group.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The PVN is one of the major sites of neuronal activation upon feeding (37), and a selective role in food intake has been demonstrated here for the MC4R (11,18,19). Therefore, we examined neuronal activation in PVN under different physiological states in both wild-type and Nckx4 mutant mice, using c-Fos expression as a marker.…”
Section: Mc4r-dependent and Ca 2ϩ -Sensitive Hyperactivation Of Pvn Nsupporting
confidence: 52%
“…The brains were post-fixed in the same fixative overnight, cryoprotected in 30% sucrose solution, embedded, and serially sectioned on a cryostat (Leica) at 20 mm thickness in the coronal plane and collected in PBS. Sections were processed for CART immunolabeling using the streptavidin-biotin-peroxidase method described earlier (Singru et al, 2007). Briefly, sections were incubated in mouse monoclonal primary antibodies against CART (54-102) diluted in 1% bovine serum albumin (Sigma) containing 0.3% Triton X-100 and 0.09% sodium azide at 1 : 5000 dilution for 2 days at 41C.…”
Section: Immunocytochemistrymentioning
confidence: 99%